Trust makes this organisation unique. Looking at the future of work through two human-centric organisations. - Sofi Kurki; Markku Wilenius (Springer, 2022)
Modes of organising have an indirect relationship with the new key technologies as enablers of new forms of organisation. The effect is two-fold: first the emergent technologies bring more efficiency to traditional organising, while at the same time inspiring ideas about new ways to approach the everyday life of organisations. Secondly, the metaphors and models based on new technology are applied to building new forms of organisational interaction. In this article we argue that the metaphors that are currently beginning to affect organisations on a larger scale are derived from networked communication technology. Pentti Malaska, a Finnish Futures Researcher, based his theory of societal change on the idea that societal forms build upon one another as a succession of needs that remain unfulfilled by the previous stage of development. He presents the next stage as society of intangible needs, where the focus of human activities will move to interaction between people. We present the results of an investigation of two case studies: Finnish IT-consultancy firm Reaktor, and Buurtzorg, a Dutch home care organisation. They both have adopted networked practices that question the traditional command and control management structures, and replace them with self-organisation, social control, and trust. In our research we are focusing especially on how technology affects the way these organisations approach their employees and clients. These empirical findings are reflected against the theory of society of intangible needs for contextualising the results, and drawing out their potential implications for the organisations and working life in the coming decades.